Editorial: coralline algae: globally distributed ecosystem engineers - Schubert, Nadine (2020)
From the early days of phycology, coralline algae (CA) have been considered the most formidable and widely distributed algae (Woelkerling, 1988). They compose an abundant and highly diverse group, divided into geniculate (articulated) and non-geniculate species (crusts and rhodolith/maërl forms). CA are present in almost every coastal ecosystem around the world, from the intertidal to mesophotic zones (Johansen et al., 1981; Steneck, 1986; Foster, 2001). They are important ecosystem engineers that provide hard, three-dimensional substrates for a highly diverse fauna and flora (Nelson, 2009), building habitats like the globally distributed rhodolith (or maërl) beds (Foster, 2001), and the large algal bioconstructions that abound in the Mediterranean (coralligenous assemblages, intertidal rims; Ingrosso et al., 2018). In addition, the CaCO3 precipitation within cell walls leads to a high fossilization potential of CA, which are considered the best fossil record among macrobenthic autotrophs since they first appeared in the Lower Cretaceous (Aguirre et al., 2000). It also makes CA major carbonate producers (van der Heijden and Kamenos, 2015), which, considering their abundance and wide distribution, gives them an important role in oceanic carbon cycling and reef building (Adey, 1998; Chisholm, 2003; Martin et al., 2006; Perry et al., 2008) and makes them a group of significant economic interest (Coletti and Frixa, 2017). Like many other marine ecosystems, CA habitats will be negatively affected by future climate change, e.g., due to reduced CA calcification/growth (Martin andHall-Spencer, 2017; Cornwall et al., 2019) that may eventually lead to ecosystem degradation and reduction of habitat complexity and biodiversity.